The Influence of Price and Vegetable Quality on Purchase Decisions in the Market: A Systematic Literature Review - Nur Fauziah; Desviana Safitri; Erlina (PT. Hidayat Muda Intelektual, 2026)
This study aims to analyze the influence of price and vegetable quality on consumers' purchasing decisions. Vegetables are a basic necessity for humans and are consumed daily, making factors such as price and quality key considerations in purchasing decisions. The vegetables sold in the market are harvested by farmers and collected by vegetable distributors. The demand for vegetables continues to increase along with public awareness of healthy lifestyles. However, higher vegetable prices can reduce consumers' purchasing power and potentially affect food security. Conversely, stable and affordable prices can increase vegetable consumption, support healthy eating habits, and strengthen household-level food security.The research method used is qualitative descriptive through a literature review. This study analyzes various previous relevant literature, both from national and international journals, totaling 20 journals, to identify patterns and common findings regarding the relationship between price, quality, and purchasing decisions. The review results show that price plays an important role in attracting initial consumer interest, while product quality plays a key role in maintaining consumer satisfaction and loyalty. This study provides a theoretical contribution by summarizing previous research findings and offers direction for future studies. Moreover, traders and market managers need to maintain price stability and improve product quality in order to sustain consumer loyalty.